2021
DOI: 10.1002/ajum.12288
|View full text |Cite
|
Sign up to set email alerts
|

How long does a transvaginal ultrasound examination for endometriosis take in comparison to a routine transvaginal ultrasound examination?

Abstract: Introduction: This study aimed to determine the additional time needed to perform an endometriosis transvaginal ultrasound (eTVUS) compared to routine transvaginal ultrasound (rTVUS). Methods: A retrospective case-control study was performed. The study group included 199 eTVUS performed between September 2019 and September 2020. The control group comprised 105 consecutive rTVUS studies performed in the same time period. The time stamps on the ultrasound images of all cases in both groups were reviewed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Although studies have suggested a good sensitivity and specificity in the diagnosis of recto-sigmoid DIE by TVS [ 23 , 43 ], it requires expertise [ 44 , 45 ] and may take significantly longer to perform compared with routine TVS [ 46 ]. Moreover, compared with MRI, it is less sensitive for upper gastrointestinal lesions (more than 16 cm from the anal margin) [ 47 ] and multifocal bowel lesions [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have suggested a good sensitivity and specificity in the diagnosis of recto-sigmoid DIE by TVS [ 23 , 43 ], it requires expertise [ 44 , 45 ] and may take significantly longer to perform compared with routine TVS [ 46 ]. Moreover, compared with MRI, it is less sensitive for upper gastrointestinal lesions (more than 16 cm from the anal margin) [ 47 ] and multifocal bowel lesions [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The SP is located deeper within the pelvis, which may influence to some extent the time needed for its visualization, compared with that of the ureter. The average duration of a routine TVS scan is about 7–8 min, whereas an extended TVS scan in a patient with pelvic DE takes 13–14 min 17 . In this context, incorporating visualization of the SP into standard gynecological pelvic TVS examination would not increase significantly the overall examination time.…”
Section: Discussionmentioning
confidence: 99%
“…The room must be set up to accommodate a longer exam time. Examinations should be performed on an adjustable examination table; tables with stirrups are preferred and adequate padding is necessary given that examinations can last up to 45 minutes 39 (though most are significantly shorter in duration than the maximum). Preparing patients in advance by ensuring that the schedulers can consistently and fully communicate what patients should expect at the time of their study and confirming they are scheduled to arrive with a full bladder, when indicated, for the transabdominal component of the scan.…”
Section: Starting An Endometriosis Ultrasound Evaluation Programmentioning
confidence: 99%